Indian Banks Mergers and Acquisitions- Conceptual Review (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
Purpose- The paper aims to provide a conceptual review of mergers and  acquisitions (M&A) in the Indian banking sector, highlighting the evolution,  strategic motivations, legal aspects, and ethical considerations of M&A activities. Design/methodology/approach- The research methodology involves a qualitative  literature review of scholarly articles, books, and relevant academic sources. The  review focuses on identifying key themes related to the motivations, processes,  and outcomes of M&A in the banking sector. Findings- The study finds that M&A activities in the Indian banking sector are  primarily driven by the need for synergy, improved managerial efficiency, growth,  and technological advancements. Synergies achieved through M&A can enhance  revenue, performance, and cost efficiency. The paper also highlights the importance  of ethical considerations and cultural integration during M&A processes to ensure  smooth transitions and maintain organizational stability. Research limitations/implications- This study is based on existing literature,  and empirical validation through case studies or primary data could further  substantiate the findings. Future research could explore the long-term impact  of M&A on financial performance and stakeholder value in the Indian banking  sector. Practical implications- The findings provide valuable insights for banking  sector stakeholders, by elucidating the strategic motivations and critical factors  influencing successful M&A transactions. Originality/value- The paper offers a detailed conceptual framework for  understanding the dynamics of M&A in the Indian banking sector, contributing  to the existing body of knowledge and guiding future research and practice in  this field.
Keywords: Mergers; Acquisitions; Banking; Sector; India; Synergy; Managerial Efficiency; Ethical Considerations; Legal Aspects